If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 8m = -3 Solving 9 + 8m = -3 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 8m = -3 + -9 Combine like terms: 9 + -9 = 0 0 + 8m = -3 + -9 8m = -3 + -9 Combine like terms: -3 + -9 = -12 8m = -12 Divide each side by '8'. m = -1.5 Simplifying m = -1.5
| 4-3w=8.5 | | 3y-6x=-33 | | F[x]=2x+12 | | -10w=15 | | x(x+4)=6(2) | | 9=v+6-2 | | (5x)=-18 | | (2x+20)=(3x-10) | | 3(2x+1)-5x=2(x+1)-3 | | (2x-20)=(3x-10) | | 15=12x^2+24x | | 4d+8-2d=6d-10 | | -12x+2y=x+2 | | 7xy-4xy+2xy+6xy+3xy-7xy= | | 14x-(3x-7)=40 | | f(n)=2*f(n-1) | | 3(3z+1)-8=40 | | -1440=-15(-15x-29) | | 8u-1=8 | | (6+k)+12=23 | | 3(2x-7)-4(x-1)= | | 2h+10=66 | | 2h+10=66 | | y-8+124=180 | | -41=5x+9 | | -1440=-15(-15x-21) | | 1.4a+10=17 | | 6x+13=5x | | n+36=5m | | (X-3)(x+4)=x^2-5x+20 | | 9+2z-8=7z+7-4z | | a(-12)=b |